Utilizando modelos SIR no estudo da propagaç\~ao e da prevalência do racismo no Brasil - Alexandre Marinho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This text presents a brief discussion on the ways in which racism spreads in Brazil, and on the reasons that make racial discrimination an extremely serious problem with implications for health, the economy, general well-being and democracy in our country. Recently, literature has treated racism as a social but also infectious disease, which would occur concomitantly with its structural nature, in the Brazilian case. With the use of very exploratory SIR models (Susceptible/Infected/Recovered), it was possible to construct scenarios in which, depending on the hypotheses about the data regarding racism, and in the absence of effective action by the Brazilian State, this social scourge could afflict us for a long time, maybe indefinitely.
Keywords: C69; I14; J15; J71; 330; racism; economics; public health; SIR models; social media